2019
DOI: 10.1186/s12864-019-5459-x
|View full text |Cite
|
Sign up to set email alerts
|

Genome changes due to artificial selection in U.S. Holstein cattle

Abstract: BackgroundThe availability of a unique unselected Holstein line since 1964 provided a direct comparison between selected and unselected Holstein genomes whereas large Holstein samples provided unprecedented statistical power for identifying high-confidence SNP effects. Utilizing these unique resources, we aimed to identify genome changes affected by selection since 1964.ResultsDirect comparison of genome-wide SNP markers between a Holstein line unselected since 1964 and contemporary Holsteins showed that the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 38 publications
(39 reference statements)
3
27
0
1
Order By: Relevance
“…The GHR-PRLR region had the largest concentration of significant effects on milk yield with peak QTL effects in C6-PTGER4 downstream of GHR . This large QTL region was within the 28-Mb region of 21–49 Mb with the strongest evidence of selection signature by the analysis of extended haplotype homozygosity (Ma et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GHR-PRLR region had the largest concentration of significant effects on milk yield with peak QTL effects in C6-PTGER4 downstream of GHR . This large QTL region was within the 28-Mb region of 21–49 Mb with the strongest evidence of selection signature by the analysis of extended haplotype homozygosity (Ma et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The Chr05 region at 83.69–102.28 Mb was 18.59 Mb in size, the Chr06 region of 83.37–93.94 Mb region was about 10.57 Mb in size, and the Chr20 region at 23.86–42.21Mb was 18.35-Mb in size. This large Chr20 QTL region was within the 28-Mb region of 21–49 Mb with the strongest evidence of selection signature by the analysis of extended haplotype homozygosity (Ma et al, 2019). In addition to the four chromosomes described in Figure 2, the additive SNP effects reported in this study involved all 29 bovine autosomes (Table S5), and identified additional regions with significant effects, including the 50.04–58.26 Mb of Chr03, the 105.45–106.36 Mb of chr05 and the 24.96–29.97 Mb of chr23 for protein yield; the 15.36–15.62 Mb of chr03 and the 64.00–71.84 Mb of Chr14 for protein percentage; the 60.23–72.08 Mb of Chr01 for daughter pregnancy rate and cow conception rate; and AFF1 for heifer conception rate.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, by comparing sperm methylomes between human and Holstein cattle, we demonstrated that genomic variants of morphology-relevant traits were consistently and significantly enriched in the evolutionarily conserved hypomethylated regions in human and cattle [26]. Furthermore, the rapidly reduced immune and reproductive capacity of dairy cattle has been observed during the strong selection for milk production over the past decades [27]. Using these cattle resources, it is possible to extrapolate genomic changes associated with immune and reproduction in cattle to further advance human biomedical researches.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to breeding for dairy production, the Holstein cow was visibly more muscular ( Figure 3). The very genome of the Holstein cow in the United States has been changed as a result of breeding by the dairy industry through artificial selection for economically important traits, resulting in the economically desired increased milk production and a regrettable concomitant decrease in fertility and immunity (Ma et al, 2019). The cow transformed by humans through biopower into a milk producer is presented to children as simply a cow.…”
Section: Thinking With a Holstein Cow Figurinementioning
confidence: 99%